Conversion of the Nitrate Nitrogen and Nitrogen Dioxide to Nitrous Oxides in Plants - Hakata, M.; Takahashi, M.; Zumft, W.; Sakamoto, A.; Morikawa, H. (Acta Biotechnologica, 2003)
Tobacco and wheat are known to emit nitrous oxide (N2O). Provided that N2O is a greenhouse gas about 300 times worse than carbon dioxide in its potential for global warming, it is an intriguing and important subject, whether this activity is commonly present in other plants. In this study, 17 plant taxa that had been cultured aseptically were fed with 15N‐labelled nitrate for one week (feeding period). The plant taxa were then transferred to a medium with non‐labelled nitrate in gas‐sealed pots and cultured for another week (emission period). The amount of labelled N2O emitted from the plants during the emission period was determined. This value reflects only a part of the capability of plants to convert nitrate to N2O, because the amount of N2O determined here does not correspond to the total N2O emission from plants, but to only an 15N‐labelled N2O fraction emitted during the emission period from nitrate taken up into the plants during the feeding period. It was discovered that all of the 17 plant taxa analysed, except for Eucalyptus viminalis, showed emission of 15N2O. The emission ranged from 0.45 ± 0.20 ng N2O/g fresh weight (kenaf) to − 0.012 ± 0.12 ng N2O/g fresh weight (Eucalyptus viminalis). This activity of converting nitrate to N2O is obviously common in plants with some exceptions. There was more than a 58‐fold variation between the highest (Hibiscus cannabinus) and the second lowest (Nicotiana tabacum) capability to convert nitrate to N2O among the 17 plant taxa. The present result indicates that the potential of plants to convert nitrate to N2O highly varies among the plant species as in the case of the assimilation of nitrogen dioxide (N2O) where more than a 600‐fold variation was observed among 217 plant taxa. A negative correlation was obtained for N2O emission and NO2 assimilation (r = 0.72). This is the first report where there was a competitive interaction between the assimilation and dissimilation activities in plants. It was also found that wild type and transgenic tobacco are able to convert NO2 to N2O when they were fumigated with 15N‐labelled NO2. However since the N2O emission values observed in this study were approximately three orders of magnitude smaller than those observed with wheat leaves, the evaluation of the environmental significance of the N2O emission by plants must await quantitative analysis using the present system to figure out the full N2O emission capability of plants.